Integrated membrane and microbial fuel cell technologies for enabling energy-efficient effluent Re-use in power plants. (15th June 2017) - Shrestha, Namita; Chilkoor, Govinda; Xia, Lichao; Alvarado, Catalina; Kilduff, James E.; Keating, John J.; Belfort, Georges; Gadhamshetty, Venkataramana
Abstract: Municipal wastewater is an attractive alternative to freshwater sources to meet the cooling water needs of thermal power plants. Here we offer an energy-efficient integrated microbial fuel cell (MFC)/ultrafiltration (UF) process to purify primary clarifier effluent from a municipal wastewater treatment plant for use as cooling water. The microbial fuel cell was shown to significantly reduce chemical oxygen demand (COD) in the primary settled wastewater effluent upstream of the UF module, while eliminating the energy demand required to deliver dissolved oxygen in conventional aerobic treatment. We investigated surface modification of the UF membranes to control fouling. Two promising hydrophilic monomers were identified in a high-throughput search: zwitterion (2-(Methacryloyloxy)-ethyl-dimethyl-(3-sulfopropyl ammoniumhydroxide, abbreviated BET SO3 − ), and amine (2-(Methacryloyloxy) ethyl trimethylammonium chloride, abbreviated N(CH3 )3 + ). Monomers were grafted using UV-induced polymerization on commercial poly (ether sulfone) membranes. Filtration of MFC effluent by membranes modified with BET SO3 − and N(CH3 )3 + exhibited a lower rate of resistance increase and lower energy consumption than the commercially available membrane. The MFC/UF process produced high quality cooling water that meets the Electrical Power Research Institute (EPRI) recommendations for COD, a suite of metals (Fe, Al, Cu, Zn, Si, Mn, S, Ca and Mg), and offered extremely low corrosion rates (<0.05 mm/yr). A series of AC and DC diagnostic tests were used to evaluate the MFC performance. Highlights: We describe an energy-efficient integrated microbial fuel cell/ultrafiltration process. Municipal wastewater primary clarifier effluent was treated for use as cooling water. High COD removal (94%) was observed. Ultrafiltration fouling was reduced by surface modification via graft polymerization. Cooling water quality criteria were met or exceeded.